158 Artificial Urinary Sphincter Reverses Weight Gain Associated with Post-Prostatectomy Incontinence. Issue 1 (1st April 2022) - Bhanvadia, R.; Dropkin, B.; Wolfe, A.; Diao, L.; Sanders, S.; Joice, G.; Roehrborn, C.; Hudak, S.; Morey, A.
ABSTRACT: Introduction: Post-prostatectomy stress urinary incontinence (PPI) is associated with decreased physical activity, a known risk factor for weight gain and negative health outcomes. The relationships of PPI severity and its surgical correction to body mass index (BMI) are unknown. Objective: We sought to examine the association between urinary incontinence severity and BMI changes before and after artificial urinary sphincter (AUS) insertion. Methods: We performed a single-institution, retrospective review of 1513 AUS and inflatable penile prosthesis (IPP) insertion cases performed between 2008 and 2020. Inclusion criteria included a history of radical prostatectomy (RP) and complete data on PPI and BMI. The IPP cohort served as a surgical control. PPI severity was assessed by pads per day (PPD). BMI data were reviewed at the following three time points: (a) at RP, (b) at urologic prosthetic surgery (UPS), and (c) 12 months post-UPS. Multivariable linear regression assessed the associations between (a) PPI severity and BMI change from RP to UPS and (b) AUS insertion and BMI change 12 months post-UPS. Results: We identified 250 men (187 AUS and 63 IPP) who met selection criteria. Men in the AUS group had a mean BMI increase between RP and UPS of + 1.0 kg/m2 versus - 0.6 kg/m2 in the IPP group (p < 0.01, duration 26.0 ± 21.8 months). Higher PPD use was associated with greater BMI gain after RP (Figure 1A, p = 0.03). On multivariable analysis, higher PPD use at the time of UPS was positively associated with BMI gain (Rho coeff. 0.50 kg/m2, p < 0.01), independent of RT and ADT. AUS insertion was independently associated with a decrease in BMI of -2.83 kg/m2 12 months post-UPS (p = 0.02) on multivariable analysis. Magnitude of incontinence improvement after AUS insertion was associated with greater BMI reduction at 12 months (Figure 1B, p = 0.04). Conclusions: PPI is associated with weight gain, and its correction via AUS insertion is associated with weight loss. Because severe PPI is a potential risk factor for weight gain and subsequent negative health outcomes, timely anti-incontinence surgery is prudent for prostate cancer survivorship care. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Boston Scientific and Coloplast